LABELING EXEMPTION APPLICATIONS IN THE FIELD OF LAND PT. BSD CITY USING AUTOCAD 2006 - Eko Budi Hartojo; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2007)
In this scientific writing, titled "Labeling EXEMPTION APPLICATIONS IN THEFIELD OF LAND PT. BSD CITY USING AutoCAD 2006 ", motivated by thedifficulty of locating the plots of land and the necessary information in a map of landacquisition in a relatively quick and precise so that more efficient and effective.Using Autocad 2006 program, which also contains many functions and compatibleenough facility in the area of liberation and land acquisitions, it is expected that thisprogram will be quite helpful in solving various problems that arise, especially in thesearch location within the map area of land acquisition and the information thereinnecessary, do not take a long time whether the new data and data long enough landthat has been released.